TINGKAT KEBUGARAN PADA ATLET BASKET PUTRI DALAM PERSIAPAN PERTANDINGAN DBL TAHUN 2024 - Dini Nurhalisa Azzahra; Susanto, Indra Himawan; Wismanadi, Himawan; Khuddus, Luthfi Abdil (Jurnal Porkes, 2024)
This study is based on fitness measurements applied to female athletes at SMA Negeri 19 Surabaya and is in preparation for the match. The purpose of this study was to examine fitness in female athletes who are members of SMA Negeri 19 Surabaya in preparing for the match. This research was conducted quantitative descriptive approach. The sample used was 12 female athletes with an age range of 16-18 years. The test instruments were multi-stage fitness test (MFT), 30 meter run, push-up and sit-up tests. Data analysis techniques are carried out by means of descriptive statistics. Based on the results of the fitness test with the MFT test, the average vo2max obtained is 35.8 ml / kg / min, meaning that this value is included in the “good” category. Meanwhile, in the 30 meter speed test the average value obtained is 2.9, meaning that the value is included in the “good” category. In the sit up test the average value obtained is 4, meaning that the value is included in the “excellent” category. In the push up test the average value obtained is 3.42, meaning that the value is in the “good” category. The conclusion is that in each component there are some athletes who have not entered the “good” category and some are already in the “good” category. Athletes who are already in the good category dominate.